12 - Mise en scène de la culture et espace public au Sénégal: https://doi.org/10.4314/ad.v35i4.70225 - Benga, Ndiouga (Africa Development, 2021)
This article traces the uneven progress of the arts and culture in Senegal under the rule of Senghor, the President-poet-philosopher, then his successors Abdou Diouf and Abdoulaye Wade, over the period running from independence to the troubled times of Structural Adjustment, little suited to cultural action. According to Senghor’s philosophy, ‘everything is culture’ and ‘all states assign to cultural policy the vocation of expressing and forging a national identity, exploiting the mythical-historical vein, embodied in cultural institutions that are intended, created and maintained by the public authorities’ [our translation]. Under Abdou Diouf and Abdoulaye Wade, cultural generosity was faced with an economic reality characterized by the depletion of resources. As of the 1980s, the cultural scène was typified by informality, a spirit of making do, the abolition of the representation and distance so dear to Senghor, and the multiplication and de-territorialization of cultural initiatives. Protests against the State and its censorship of public space, from the 1970s to the late 1990s, can be analyzed in the context of an attempt to develop an alternative popular culture, from the Front Culturel, to film (Sembène)and the independent artists of the Village des Arts and Agit-Art.